Therapeutic options in lung neuroendocrine tumors: between established concepts and new hopes. Issue 7 (August 2019) - Brighi, Nicole; Lamberti, Giuseppe; Manuzzi, Lisa; Maggio, Ilaria; Campana, Davide
Abstract : Typical (TC) and atypical (AC) carcinoids are low-grade neuroendocrine tumors (NETs) of the lung and, are neglected diseases in respect of both high-grade NETs of the lung (i.e. small-cell lung cancer and large-cell neuroendocrine carcinoma) and gastroenteropancreatic (GEP)-NETs. AC and TC account for 2 and 0.2% of all thoracic malignancies, respectively, and have a 12.9% chance of metastatic spread at diagnosis, reaching up to 20% during disease history. There are very few trials specifically designed for lung NETs, and therapeutic options are mainly derived by studies carried out in patients with GEP-NETs. We report a case of a patient affected by AC progressed to available standard treatments who received off-label treatment with sunitinib, a well-known multitarget tyrosine-kinase inhibitor with marked antiangiogenic activity, used routinely for the treatment of GEP-NETs. During treatment, the patient required the administration of an alternative schedule to improve tolerability, with benefit, and achieved a partial response according to the RECIST criteria, which is unusual in NETs. We critically reviewed available data supporting the use of somatostatin analogs, chemotherapy, and target therapies (everolimus and sunitinib) in advanced lung NETs. In the review, ongoing trials in lung NETs and future developments in this research field are also discussed.